2020
DOI: 10.3354/meps13432
|View full text |Cite
|
Sign up to set email alerts
|

Integration of temporal environmental variation by the marine plankton community

Abstract: Theory and observations suggest that low frequency variation in marine plankton populations, or red noise, may arise through cumulative integration of white noise atmospheric forcing by the ocean and its amplification within food webs. Here, we revisit evidence for the integration of stochastic atmospheric variations by comparing the power spectra of time series of atmospheric and oceanographic conditions to the population dynamics of 150 plankton taxa at Station L4 in the Western English Channel. The power sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 89 publications
(127 reference statements)
2
17
0
Order By: Relevance
“…Microscopic organisms are indeed known to be involved in complex and dynamical networks of interactions (i.e., grazing, parasitism, mutualism, quorum sensing, etc; Kivi et al, 1993;Dakos et al, 2009;Platt et al, 2009;Bjorbaekmo et al, 2020) that are tightly regulating the dynamics of individual species within the whole community structure. Recently, in the WEC at L4 station predator-prey interactions were investigated supporting our hypothesis that they play a role in influencing temporal changes in plankton populations (Barton et al, 2020).…”
Section: Environmental Versus Community Intrinsic Drivers Of Protistan Plankton Seasonal Dynamicsmentioning
confidence: 54%
See 1 more Smart Citation
“…Microscopic organisms are indeed known to be involved in complex and dynamical networks of interactions (i.e., grazing, parasitism, mutualism, quorum sensing, etc; Kivi et al, 1993;Dakos et al, 2009;Platt et al, 2009;Bjorbaekmo et al, 2020) that are tightly regulating the dynamics of individual species within the whole community structure. Recently, in the WEC at L4 station predator-prey interactions were investigated supporting our hypothesis that they play a role in influencing temporal changes in plankton populations (Barton et al, 2020).…”
Section: Environmental Versus Community Intrinsic Drivers Of Protistan Plankton Seasonal Dynamicsmentioning
confidence: 54%
“…A seasonal thermocline, occurring from May to October, is only reported in its western entrance, offshore and along the UK coasts (Pingree and Griffiths, 1980). In these seasonally stratified waters sampled regularly by the Plymouth L4 Western Channel Observatory (Pingree and Griffiths, 1978), plankton temporal dynamics has been recently explored (Widdicombe et al, 2010;Edwards et al, 2013, Barton et al, 2020 and both seasonal and inter-annual changes in abundance were observed along with significant long-term changes in community composition and reorganization of plankton food web (Molinero et al, 2013;Reygondeau et al, 2015). The temporal dynamics of planktonic communities in the permanently well-mixed waters that characterize the French coasts of the WEC have been less intensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The larger the amount of noise added, the larger the assemblage size must be to achieve high predictability. Given that there will always be a range of sources of measurement error in phytoplankton time series such as at L4 (see Barton et al, 2020 ), this model result suggests that aggregating across multiple species may be a desirable strategy for making predictions.…”
Section: Resultsmentioning
confidence: 95%
“…using the Bayesian Information Criterion yields the same number of changepoints almost everywhere but different models). The overall incidence of changepoints may be more important than their specific magnitude, as recent work suggests that even small-amplitude ecological and biogeochemical changes can have appreciable consequences (Stock et al, 2014a;Barton et al, 2020).…”
Section: Changepoint Analysismentioning
confidence: 99%
“…Rapid changes in marine plankton populations may occur when changes in environmental conditions generate a sudden forcing on the community (Muller-Karger et al, 2019;Ardyna et al, 2014), or when gradual changes in environmental conditions provoke a nonlinear response (Scheffer et al, 2001;Stock et al, 2014a). With or without environmental forcing, rapid changes can also emerge from the internal dynamics of plankton communities (Di Lorenzo & Ohman, 2013;Barton et al, 2020;Huisman & Weissing, 1999). Because of the challenges of collecting long-term and broad-scale measurements of plankton populations (Benway et al, 2019), much remains unknown about how frequent abrupt changes are in the lower trophic levels of pelagic marine ecosystems, how abrupt changes differ with trophic status or organism size (Barton et al, 2020), how abrupt changes in plankton populations correspond to those in physical or chemical environmental conditions, or how their frequency and distribution will change (or already are changing) with climate change (Beaulieu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%